Fatigue and Crack-growth Analyses under Giga-cycle Loading on Aluminum Alloys - Newman, J.C. (Procedia engineering, 2015)
Stress-life (S-N) data from the literature on uniaxial-loaded specimens made of 2024-T351 aluminum alloy and subject to constant-amplitude loading are used to support the crack-growth concept to calculate the fatigue behavior into the giga-cycle fatigue regime using initial flaw sizes consistent with micro-structural discontinuities in the material. Fatigue test data from the literature on uniaxial-loaded specimens made 7075-T6 under superimposed low- (5Hz) and ultra-high- (20kHz) cycle (sine-on-sine) fatigue loading are used to study the crack-growth concept for predicting fatigue behavior under giga-cycle fatigue conditions. Fatigue behavior under giga-cycle loading conditions was modelled fairly well with the crack-growth concept.